2009
DOI: 10.1208/s12249-009-9246-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and In Vitro Evaluation of Solid Dispersions of Total Flavones of Hippophae rhamnoides L.

Abstract: The purpose of this study was to enhance the dissolution of total flavones of Hippophae rhamnoides L. (TFH) by solid dispersions consisting of the drug and a polymeric carrier, poloxamer 188 (PXM). The solvent evaporation method was used to prepare solid dispersions. A 3(2) full-factorial design approach was used for optimization wherein the amount of solvent (X(1)) and the drug-to-polymer ratio (X(2)) were selected as independent variables and the percentage of TFH dissolved in 10 min (Q(10)) was selected as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…The relevant bioavailability of quercetin was enhanced 3.1 times and 2.4 times when encapsulated in solid dispersions (SD) and self‐emulsions (SE), respectively after oral administration in beagle dogs (Duan and others ), and in the case of oral administration in rats, this bioavailability of quercetin was boosted to 3.16 (in SD form) and 1.55 (in SE form) times, separately (Zhao and others ). Compared with Duan (Duan and others ) and Xie's (Xie and others ) work on solid dispersion formulations (composed of Poloxamer 188 and ethanol), our study contained less surfactants but performed a comparable bioavailability improvement, all of which could increase the bioavailability of quercetin around 3.0‐fold of those in suspension. Although similar components (MCT, CrEL, and Trans HP at ratios of 13.26: 60.38: 26.36) were used to form self‐microemulsions as a comparison to Duan and Zhao's development (SE composed of MCT CrEL, and 1,2‐propanediol at ratios of 5:57:38; Zhao and others ; Duan and others ), quite different enhancement levels were existed.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The relevant bioavailability of quercetin was enhanced 3.1 times and 2.4 times when encapsulated in solid dispersions (SD) and self‐emulsions (SE), respectively after oral administration in beagle dogs (Duan and others ), and in the case of oral administration in rats, this bioavailability of quercetin was boosted to 3.16 (in SD form) and 1.55 (in SE form) times, separately (Zhao and others ). Compared with Duan (Duan and others ) and Xie's (Xie and others ) work on solid dispersion formulations (composed of Poloxamer 188 and ethanol), our study contained less surfactants but performed a comparable bioavailability improvement, all of which could increase the bioavailability of quercetin around 3.0‐fold of those in suspension. Although similar components (MCT, CrEL, and Trans HP at ratios of 13.26: 60.38: 26.36) were used to form self‐microemulsions as a comparison to Duan and Zhao's development (SE composed of MCT CrEL, and 1,2‐propanediol at ratios of 5:57:38; Zhao and others ; Duan and others ), quite different enhancement levels were existed.…”
Section: Resultsmentioning
confidence: 83%
“…It has been demonstrated that the promising absorption enhancement of TFH had reached to a certain extent by adding absorption enhancers, such as phytic acid and sea buckthorn oils (Suomela and others ; Xie and others ) or by formation of tablets, capsules, and solid dispersions, β‐cyclodextrin complex as well as self‐emulsifying system (Yue and others ; Xie and others ; Duan and others ). Of all these reported and other solubilization approaches, nanocarriers to encapsulate drugs, and nutraceuticals have been drawn much attention, such as microemulsions, nanoemulsions, micelles, and solid lipid nanoparticles (Bilia and others ).…”
Section: Introductionmentioning
confidence: 99%
“…The XRD pattern of the physical mixture showed characteristics diffraction peaks of 14°, 24°, and 35°, but with lesser intensity. However, the absence of sharp diffraction peaks was noticeable in optimized solid dispersions, which indicate the amorphous embedding or molecular dispersibility of drug within polymer matrix [37].…”
Section: Xrd Studiesmentioning
confidence: 95%
“…Nature of the solvent and the rate of evaporation of the solvent are the critical factors which can affect the formed mass (Xie et al, 2009). The most important advantage of this method is that thermal decomposition of the drugs can be avoided as low temperature is required for the evaporation of the organic solvents.…”
Section: Introductionmentioning
confidence: 99%